2010
DOI: 10.1161/hypertensionaha.109.135665
|View full text |Cite
|
Sign up to set email alerts
|

LIM and Cysteine-Rich Domains 1 Regulates Cardiac Hypertrophy by Targeting Calcineurin/Nuclear Factor of Activated T Cells Signaling

Abstract: Abstract-LIM domain proteins are important regulators in cell growth, cell fate determination, cell differentiation, and remodeling of the cell cytoskeleton. LIM and cysteine-rich domains 1 (Lmcd1) is a novel protein that contain 2 LIM domains with regular spacing in the carboxy-terminal region. However, its roles in cardiac growth remain unknown. Here, we investigated whether Lmcd1 regulates cardiac hypertrophy in vitro and in vivo and elucidated the underlying molecular mechanisms. We used primary cultured c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…Consistent with this notion, blocking MEK-ERK1/2 signaling by U0126 rescued deteriorative cardiac dysfunction and dilation in Rgs5 mutant mice, indicating that the inhibitory effects of Rgs5 on cardiac hypertrophy are mediated through MEK-ERK1/2 signaling. Pathological cardiac hypertrophy is accompanied by interstitial and perivascular fibrosis and approaches to limit collagen deposition in the heart have been limited to date (15)(16)(17)(18). The present study revealed that Rgs5 blocks cardiac fibrosis in vivo and inhibits collagen synthesis in vitro.…”
Section: Discussionmentioning
confidence: 52%
“…Consistent with this notion, blocking MEK-ERK1/2 signaling by U0126 rescued deteriorative cardiac dysfunction and dilation in Rgs5 mutant mice, indicating that the inhibitory effects of Rgs5 on cardiac hypertrophy are mediated through MEK-ERK1/2 signaling. Pathological cardiac hypertrophy is accompanied by interstitial and perivascular fibrosis and approaches to limit collagen deposition in the heart have been limited to date (15)(16)(17)(18). The present study revealed that Rgs5 blocks cardiac fibrosis in vivo and inhibits collagen synthesis in vitro.…”
Section: Discussionmentioning
confidence: 52%
“…In an attempt to elucidate the mechanisms underlying the antifibrotic effect of cFLIP, we analyzed key components of TGF-␤1-Smad signaling, which is a crucial pathway in the regulation of fibrosis. 10 Our results demonstrated that cFLIP abrogates Smad 2 phosphorylation and Smad 2/3 translocation in both cultured cardiac fibroblasts and hypertrophied hearts, thus inhibiting collagen synthesis and fibrosis. Recent studies suggest that the TGF-␤1/Smad pathway can be regulated by the MEK-ERK1/2 pathway.…”
Section: Et Al Cflip Inhibits Cardiac Hypertrophysupporting
confidence: 50%
“…Towards exploring the mechanisms of VSMC multiplication during restenosis, we found that thrombin induces the expression of LMCD1 in HASMCs. Previous studies have shown that LMCD1 represses transcriptional factor GATA6 and promotes cardiac hypertrophy (11,12). In line with its role in cardiac hypertrophy, the present findings show that LMCD1 expression is required for thrombin-induced HASMC replication.…”
Section: Discussionsupporting
confidence: 90%
“…Although the cellular functions of many LIM proteins have been studied (10), there are only a limited number of reports on the biological functions of LMCD1. It was reported that LMCD1 plays a role in the development of cardiac hypertrophy (11). Another study suggests that LMCD1 acts as a transcriptional repressor for GATA6, a zinc-finger transcription factor, in lung and cardiac tissues (12).…”
mentioning
confidence: 99%